Atrial fibrillation and sympatho–vagal imbalance: from the choice of the antiarrhythmic treatment to patients with syncope and ganglionated plexi ablation. (26th April 2023) - Rebecchi, Marco; De Ruvo, Ermenegildo; Sgueglia, Marianna; Lavalle, Carlo; Canestrelli, Stefano; Politano, Alessandro; Jacomelli, Ilaria; Golia, Paolo; Crescenzi, Cinzia; De Luca, Lucia; Panuccio, Marco; Fagagnini, Alessandro; et al.
Abstract: For several years, the autonomic nervous system has played a central role in the pathophysiological mechanism of atrial fibrillation (AF), so much so that it has been considered one of the cornerstones of Coumel's triangle. The clinical and therapeutic management of AF secondary to sympatho–vagal imbalance represents one of the most important examples of how precision medicine should be applied. Increasing knowledge of this kind of arrhythmias has made it possible to select specific antiarrhythmic drugs and to diversify their use according to vagal or adrenergic AF forms. Ablative strategies, such as cardioneuroablation and non-direct cardiac neuromodulation methods (such as renal denervation and peripheral vagal stimulation), have gradually emerged. In the possibly near future, there will be a development of new acquisitions regarding new pharmacological therapeutic strategies and gene therapy. Finally, finding an AF in patients experiencing syncopal episodes opens a whole chapter regarding interesting, but also complex, diagnostic and therapeutic strategies, ranging from neurally mediated forms to convulsive seizure that could also increase the risk of sudden death.